1st metatarso-phalangeal joint arthroplasty with ROTO-glide implant. Issue 3 (September 2017) - Tunstall, C.; Laing, P.; Limaye, R.; Walker, C.; Kendall, S.; Lavalette, D.; Mackenney, P.; Adedapo, A.; Al-Maiyah, M.
Highlights: A multicentre service evaluation of ROTO-glide 1st MTPJ replacement. Low complication rate with no revisions during follow-up period. Good postoperative outcomes with improvement in functional scores. Abstract: Background: Total joint replacement of the 1st metatarso-phalangeal Joint (MTPJ) has been controversial as arthrodesis remains a good option for patients with end stage 1st MTPJ arthritis. We present a multi centre service evaluation of the ROTO-glide device Methods: 33 ROTO-glide procedures were carried out in 30 patients across 7 sites within the UK. Exclusion criteria — hallux valgus and arthritis, age below 45 years and over 80 years, inflammatory joint disease. Patient assessed pre and post operatively with AOFAS and Oxford forefoot (MOXFQ) scores and plain radiographs. All patients carried out the same post operative protocol Results: Average age at patients was 58.6 years (45–77). Follow up average was 16.9 months (12–29). Pre-op AOFAS scores average 41.4 (17–67) and post op average 76 (29–100) and the MOXFQ summary index decreased from an average of 43 (20–64) pre op to an average of 17 (0–51) post op. Average total range of motion pre operatively was 32° and post operatively was 61°. There were 2 post operative complications but no revisions were necessary. Conclusions: The early results of this multi centre service evaluation of the ROTO-glide 1st MTPJ replacement support its continued use and evaluation of the prosthesis further